Ultra-wideband antenna array design for target detection - Kasi B.; Chakrabarty C.K. (2023)
In this paper, a four-element microstrip antenna array is presented. The array is composed of Wilkinson power dividers which act as feed network along with Dolph-Chebyshev distribution and four-identical patch antenna elements. The array elements are properly designed to have a compact size and constant gain against frequency. The simulated results show good agreement with the measured results for the fabricated antenna array. Measurement shows that the array has a peak gain of more than 12dBi with side-lobe level of -15 dB at 6 GHz. These characteristics make the antenna array suitable for UWB directional uses.